Pelatihan Menjadi MC (Master of Ceremony) Pemula Bagi Anak Anak Untuk Menambah Kepercayaan Diri Siswa SD Negeri Ragunan 05 Jakarta Selatan - Dwi Kartikawati; Nurhasanah Nurhasanah (Journal on Education, 2023)
Speaking skill is an important factor that is needed by humans as social beings. public speaking skills need to be possessed by everyone, including elementary school children. By being taught speaking skills, these children will increase their self-confidence. One of these speaking skills is taught with the skills to become an MC (Master of Ceremony). Elementary school children are often expected to become MCs in practice, namely those who MC have an important role in a series of events, because an MC is someone who is responsible for running an event, for example in ceremonies, in religious activities and so on. So training activities to become beginner MCs for elementary school children are urgent. This activity was carried out at Ragunan 05 Elementary School, South Jakarta which was aimed at grade 5. It is hoped that after this MC training activity, Elementary School 05 students in Ragunan have the skills to present an event, then students practice speaking and practice good response and politeness when expressing something as well as train thoughts and speech in a unified manner in conveying ideas in a chronological and structured manner so as to increase students' self-confidence.